Experiences of South Korean mothers of children with medical complexity under long‐term hospitalization - Ji Young An; So‐Hi Kwon; Hye Ri Choi (Wiley, 2023)
Abstract Aims To explore the experiences of South Korean mothers of their children with medical complexity under long‐term hospitalization. Design A qualitative descriptive using thematic analysis. Methods Seven South Korean mothers of children with medical complexity underwent semi‐structured interviews between February and April 2021. Data were analysed by six phases of thematic analysis. The consolidated criteria for reporting qualitative research guidelines were applied in the conduct of the research. Results Mothers of children with medical complexity experienced a journey beginning from within their vacillating minds towards the outside world. The mother's journey during the hospitalization of their children with medical complexity began from within their vacillating minds towards achieving resilience. The mothers received various support from the family, society and hospital staff during this period of vacillation. When the mothers achieved resilience, they in turn provided support to other mothers as an act of solidarity.